Performance study of digital communication over high frequency channel - Andrews, Jinto (2013)
This report focuses on the performance study of digital communication on high frequency channel using Matlab simulations. Due to current limitations in the available frequency spectrum, it becomes necessary to harvest higher frequency bands for communication purposes. One of the available high frequency channels is the Ionospheric channel, which is well known for its uncertain behavior. So it is good to have a thorough study about the channel and the performance of different modulation schemes over this channel. We will look into the different concepts involved in this study and gain a holistic understanding of the system. Different modulations schemes like BPSK and BFSK are tested over different types of channels like additive white Gaussian noise channel, Rayleigh channel, Rician channel and finally the high frequency Ionospheric channel. High frequency channel is a modified version of multi-path Rayleigh fading channel. Because of the multi-path effect and turbulence in the ionosphere, it results in very bad bit error rates for the modulation schemes used. Different techniques are introduced to improve the bit error rate performance. We will explore on these techniques, like equalization and diversity, to improve the bit error rate performance.